![\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\huge{\mathtt{\color{purple}{✤ QUESTION ✤ }}}\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\: \:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\huge{\mathtt{\color{purple}{✤ QUESTION ✤ }}}\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:](https://tex.z-dn.net/?f=%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5Chuge%7B%5Cmathtt%7B%5Ccolor%7Bpurple%7D%7B%E2%9C%A4+QUESTION+%E2%9C%A4+%7D%7D%7D%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A)
if p(X) = ax² + bx + c = 0 and a + c = b . Find its Zeroes.
❌❌Don't give wrong answers❌❌
✅✅Correct answer will be marked as brainliest ✅✅
Answers
Answered by
22
Given:-
- p(x) = ax² + bx + c = 0 and
- a + c = b
Step by step Explanation:-
p(x) = ax²+ bx + c
put x=1
p (1) = a + b + c
but a + b + c = 0
so,p(1) = 0
so, x = 1
Answered by
0
Answer:
.
Step-by-step explanation:
hope this helps u thank u
Attachments:
![](https://hi-static.z-dn.net/files/df1/c07f99a4e59f71905461d7624d9fc9fa.jpg)
![](https://hi-static.z-dn.net/files/d46/9384300ced7e4670d3139fd8085e6f62.jpg)
Similar questions